Comparação entre os efeitos da massoterapia e da placa miorrelaxante de Michigan sobre a dor e o sinal eletromiográfico de pacientes bruxistas com DTM: ensaio clínico controlado e randomizado - Andrade, Daniel Ventura de (2009)
Due to the multifactorial etiology of temporomandibular disorder (TMD), it persists as a difficult challenge for health professionals towards its diagnosis and treatment. As a consequence of its high prevalence and damaging potential, it is essential that we understand its peculiarities and features, and the electromyography is the only exam that assesses possible muscle alterations derived from bruxism. This study comprised of a randomized, double blind, controlled clinical trial, where we compared the effects of massage therapy with that of the Michigan type occlusal splint and with the combined therapy utilizing both the massage and the mentioned splint on the electromyographic signal of bruxist patients with temporomandibular disorder. The sample comprised of 60 subjects was randomly divided into 4 groups. Of these, 3 experimental groups comprised of subjects with signs and symptoms of bruxism and temporomandibular disorder, which were treated with massage therapy (group A), Michigan type occlusal splint (group B) and both massage therapy and the occlusal splint (group C), respectively, for four weeks. The control group (group D) comprised of symptom-free subjects of bruxism or temporomandibular disorder, and they did not receive any type of treatment. All subjects were submitted to the EMG assessment of masticatory muscles and pain, pre and post treatment. The results showed that only the groups A and C, presented a significantly decrease in pain (p=0,0008), and combination therapy presented the most significant improvement (69.58%). However, significant differences were not observed in any group regarding the electrical activity of the assessed muscles. We concluded that only use Michigan type occlusal splint for four weeks did not present significant differences regarding the electromyographic signal and pain of bruxist patients with temporomandibular disorder. The massage treatment and your association with the Michigan occlusal splint treatment can reduce pain